Effects of thermal processing methods on the edible quality, nutrition, and metabolites of shrimp of Metapenaeus ensis - Miao Xiong; Hejiang Zhou; Rui-Xue Yu; Jun-Quan Chen; Shuangping Wang; Wen Xu; Yang Tian; Ling-Yan Su (Food Production, Processing and Nutrition)
Abstract Thermal processing significantly impacts the quality and characteristics of shrimp meat. In this study, we employed essential physicochemical composition determination, texture analysis, sensory evaluation, an electronic tongue assay, and UHPLC-Q Exactive-MS/MS metabolomics to investigate changes in the edible quality and metabolites of the meat of Metapenaeus ensis meat subjected to different thermal processing procedures (air frying, boiling, frying, drying). A total of 79 key differentially abundant metabolites affecting the eating quality of shrimp were identified. The different metabolites were significantly correlated with the color, meat quality, pH value, and nutritional components of the shrimp (p < 0.05). The primary metabolites affecting shrimp flavour were AMP, D-pyroglutamic acid, succinic acid, and benzoic acid. The flavour richness and sensory evaluation scores of shrimp e-tongues subjected to air frying were the highest. Purines and heterocyclic amines produced in the boiling treatment group are the least harmful and healthiest heat treatment methods. Drying treatment is the most nutritious heat treatment method for ensuring flavour. This study clarified the molecular mechanism of the quality change in shrimp meat after heat treatment. This study provides a theoretical basis for optimizing and selecting Metapenaeus ensis processing technology. Graphical Abstract